Care Ethics, Democratic Citizenship and the State - Urban, Petr; Ward, Lizzie (International Political Theory, 2020)
This book reflects on theoretical developments in the political theory of care and new applications of care ethics in different contexts. The chapters provide original and fresh perspectives on the seminal notions and topics of a politically formulated ethics of care. It covers concepts such as democratic citizenship, social and political participation, moral and political deliberation, solidarity and situated attentive knowledge. It engages with current debates on marketizing and privatizing care, and deals with issues of state care provision and democratic caring institutions. It speaks to the current political and societal challenges, including the crisis of Western democracy related to the rise of populism and identity politics worldwide. The book brings together perspectives of care theorists from three different continents and ten different countries and gives voice to their unique local insights from various socio-political and cultural contexts.